2000
DOI: 10.1039/b002354j
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the continuous distribution of binding sites in molecularly imprinted polymers

Abstract: Reported is the first affinity spectrum (AS) [number of binding sites (N) vs. association constant (K)] for a non-covalently imprinted polymer. The AS method yields the distribution of sites over a continuous range of binding constants and characterizes the heterogeneity present in imprinted polymers better than current methodologies. To demonstrate the generality of the AS method, the distributions for three different imprinted polymers (two of which were taken from the literature) were calculated from their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
121
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 35 publications
(4 reference statements)
5
121
1
1
Order By: Relevance
“…The plot for the binding of vancomycin by the imprinted cyclodextrin polymer in water has been reported by Asanuma et al [36]. Umpleby II et al [37] reported the first quantitative measure of the continuous distribution of association constants in a noncovalently imprinted polymer. The resulting binding parameters were compared with those determined by the popular Scatchard plot.…”
Section: Chromatographic and Batchwise Guest-binding Methodsmentioning
confidence: 93%
“…The plot for the binding of vancomycin by the imprinted cyclodextrin polymer in water has been reported by Asanuma et al [36]. Umpleby II et al [37] reported the first quantitative measure of the continuous distribution of association constants in a noncovalently imprinted polymer. The resulting binding parameters were compared with those determined by the popular Scatchard plot.…”
Section: Chromatographic and Batchwise Guest-binding Methodsmentioning
confidence: 93%
“…A possible solution for the latter is the analysis of limiting slopes according to scatchard plots, which can be characterized as type of bi-Langmuir equation [90]. Hence, the comparison of binding properties of different or even of the same MIP by homogeneous models is difficult [78].…”
Section: Affinity Distribution Analysismentioning
confidence: 99%
“…The idea is to transform the data to create a linear graph and use the method of least squares to find the parameters of the isotherm. Examples include Scatchard plots of binding data [70,77,78] and linearized forms of Freundlich and Langmuir equations [69,75,79,80]. It is very common to express the isotherm models in linear form.…”
Section: Isotherm Modelsmentioning
confidence: 99%
“…In reality, the Langmuir model does not adequately describe most MIPs. Shimizu et al have therefore introduced a method that allows the affinity distribution of a MIP to be assessed, assuming a continuous range of affinity constants (7 ). As a remedy to this binding site heterogeneity, it has been proposed to chemically block low-affinity sites while the high-affinity sites are occupied by the template and thus protected (8).…”
Section: New Imprinting Approachesmentioning
confidence: 99%